PENGARUH PEMBERIAN AROMATERAPI LAVENDER TERHADAP PENURUNAN NYERI PADA PERSALINAN KALA I - Novita, Lintang (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Aromatherapy is a number of non-pharmacological techniques that can increase maternal comfort during labor and have an influence on effective coping with the labor experience. Purpose: to determine the effect of lavender aromatherapy on reducing pain in labor in the first stage. Methods: This study was conducted by searching the literature in several articles such as PubMed and Google Scholar according to predetermined criteria. Result: that in the first article there is an effect that occurs on the intensity of pain in labor in the first stage by providing lavender aromatherapy techniques, namely reduced pain between the latent phase and the early active phase is significantly lower in the group given aromatherapy. And in the second article there was also a decrease in labor pain during the active phase 1 after being given lavender aromatherapy with a pvalue = 0.000. Conclusion: there is an effect that occurs in reducing pain during the first stage of labor by providing lavender aromatherapy techniques.